Vertical Transmission of H9N2 Avian Influenza Virus in Goose - Yu, Guanliu; Wang, Aihua; Tang, Yi; Diao, Youxiang (Frontiers in Microbiology, 2017)
During a study on high mortality cases of goose embryo in Shandong Province, China (2014–2015), we isolated an H9N2 avian influenza virus (AIV) strain (A/goose/Shandong/DP01/2014, DP01), which was supposedly the causative agent for goose embryo death. Sequence analysis revealed that DP01 shared 99.9% homology in the HA gene with a classic immune suppression strain SD06. To study the potential vertical transmission ability of the DP01 strain in breeder goose, a total of 105 Taizhou breeder geese, which were 360 days old, were equally divided into five groups (A, B, C, D, and E) for experimental infection. H9N2 AIV (DP01) was used for inoculating through intravenous (group A), intranasal instillation (group B), and throat inoculation (group C) routes, respectively. The geese in group D were inoculated with phosphate buffer solution (PBS) and those in group E were the non-treated group. At 24 h post inoculation, H9N2 viral RNA could be detected at vitelline membrane, embryos, and allantoic fluid of goose embryos from H9N2 inoculated groups. Furthermore, the HA gene of H9N2 virus from vitelline membrane, embryo, allantoic fluid, and gosling shared almost 100% homology with an H9N2 virus isolated from the ovary of breeder goose, which laid these eggs, indicating that H9N2 AIV can be vertically transmitted in goose. The present research study provides evidence that vertical transmission of H9N2 AIV from breeding goose to goslings is possible.